Ultra-sonographic image of ovarian mass and increased CA 19-9 levels as a pre-operative diagnostic predictor of mature cystic teratoma of ovary - Malla, Sameer; Fan, Jiangtao; Vaidya, Tripti (Journal of Kathmandu Medical College, 2018)
Introduction: Mature cystic teratoma of ovary, categorized as germ cell tumor is commonly seen in females of reproductive age group. The main aim of this study is to evaluate the serum level of CA 19-9 in those patients.Methods: A prospective study on 65 patients at First Affiliated Hospital, Guangxi Medical University, China within the period of one year. Patients underwent pelvic examination, ultra-sonograph and evaluation of serum level of CA 19-9, CA 125, CEA, AFP and SCCA prior to surgery. Following the surgery, samples were subjected for histo-pathological analysis where confirmatory diagnosis of Mature Cystic teratoma of ovary was established. Serum CA 19-9 was then re-analyzed following surgical removal of the tumor.Results: Mean age of patients with mature Cystic teratoma was 32.5±12.1 years (range 15-71). Mean tumor diameter was 5.8±2.4cm (range 2.3-12.2). Serum level of CA19-9 was the only tumor marker with a mean serum level (49.9±73.4IU/ml) above the cut-off value and its elevated rate was 30.76 %. Rate of bilateral tumors was 16.9%. The tumor size was significantly higher in patients with elevated CA 19-9 than those with normal CA 19-9. There was significant difference in the serum level of CA 19-9 before and after the surgery (p